Systematic review of the recovery of biogas from solid waste from Portillo - Hurtado Noriega, Carlos (2023)
In the world there is a growing awareness about the use of clean energy to reduce the rates of environmental pollution caused by gases that cause global warming, in that sense this research focuses on the use of biogas produced by solid waste from landfills as a source of renewable energy. In the particular case of the Portillo Grande landfill from Lurín, the confined solid waste produces large amounts of biogas that are burned manually before it goes outside, without its energy value being used. A qualitative approach was used as a study methodology, developing a systematic review of the available literature to determine through the valorization of biogas with parameters applicable to future landfills in Peru.It is concluded that the Portillo Grande landfill offers a great potential for biogas that can be used as a renewable energy source, in addition to contributing to the mitigation of greenhouse gases. It is essential to continue with research on the use of biogas with the impulse of private investment, complemented by a State political decision for its promotion and financing.